IVF pregnancy after kidney transplantation: clinical case and literature review - E. I. Prokopenko; V. M. Guryeva; V. A. Petrukhin; K. V. Krasnopol’skaya; F. F. Burumkulova; D. V. Gubina (Вестник трансплантологии и искусственных органов)
Kidney transplantation (KT), the optimal treatment for stage 5 chronic kidney disease (CKD), restores impaired fertility in most women of reproductive age. However, infertility occurs in some patients after successful KT. We present our own experience of overcoming secondary tubal infertility by in vitro fertilization (IVF). The patient was a 36-year-old with a transplanted kidney, who had lost two pregnancies in the past due to severe preeclampsia (PE). After the second attempt on cryo-thawed embryo transfer against the background of hormone replacement therapy, one embryo was transferred into the uterus, resulting in pregnancy. Gestational diabetes mellitus (GDM) was diagnosed in the first trimester, and a diet was prescribed. Immunosuppression with tacrolimus, azathioprine and methylprednisolone, prophylaxis of PE with low molecular weight heparin and antiplatelet drugs were administered during pregnancy. Elective cesarean section was performed at 37–38 weeks and a healthy boy was born, weighing 2760 g (25th percentile), 48 cm tall (36th percentile). A stay in the neonatal intensive care unit was not required. The baby is growing and developing normally, the mother’s renal graft function is satisfactory. So, IVF can be successfully used in post-KT patients with infertility issues, provided that the IVF program is carefully controlled, and the pregnancy is managed in a multidisciplinary manner.